The Visits to Rhodes of Karol Lanckoroński (1848-1933) - Mielczarek, Mariusz; Stefanakis, Manolis I. (Acta Archaeologica Lodziensia, 2021)
Archaeological expeditions to Pamphilia and Pisidia, 1882/1883 and 1884, directed and financed by Karol Lanckoronski (1848-1933), on their to Asia Minor twice visited Rhodes, forming their temporary base in Rhodes and Lindos. Photographers were among members of both archaeological expeditions. Thanks to their activity Lanckoroński’s archive – at present in the Archive of the Polish Academy of Arts and Sciences – has preserved unique photos from Rhodes. The article is also the presentation of some unique visual documentation of 19th century Rhodes.